2015
DOI: 10.1080/23744731.2015.1023162
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of occupancy-based energy-efficient climate control of VAV terminal units

Abstract: Results are presented from a nearly week-long experimental evaluation of a scalable control algorithm for a commercial building HVAC system based on real-time measurements of occupancy obtained from motion detectors. The control algorithm decides air flow rate and amount of reheat for each variable air volume terminal box based on real-time measurements of occupancy and space temperature. It is a rule-based controller, so the control computations are simple. The experiments showed that the proposed controller … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…On the other hand, occupancy-centric control adjusts the indoor environment based on occupancy (i.e., presence/absence or occupant counts). For example, artificial lighting operation (e.g., [27] , [28] , [29] ) and HVAC equipment schedules and airflow setpoints (e.g., [30] , [31] , [32] , [33] , [34] , [35] ) can be altered based on the presence/absence of occupants or the number of occupants present, thus reducing lighting and conditioning loads if occupants are absent or the zones of interest are only partially occupied. Both types of OCC ultimately require a supervisory control program within the BAS to modulate dampers, valves, and/or other actuators to produce the desired equipment operation necessary to meet occupants’ needs as determined by OCC.…”
Section: Background and Previous Workmentioning
confidence: 99%
“…On the other hand, occupancy-centric control adjusts the indoor environment based on occupancy (i.e., presence/absence or occupant counts). For example, artificial lighting operation (e.g., [27] , [28] , [29] ) and HVAC equipment schedules and airflow setpoints (e.g., [30] , [31] , [32] , [33] , [34] , [35] ) can be altered based on the presence/absence of occupants or the number of occupants present, thus reducing lighting and conditioning loads if occupants are absent or the zones of interest are only partially occupied. Both types of OCC ultimately require a supervisory control program within the BAS to modulate dampers, valves, and/or other actuators to produce the desired equipment operation necessary to meet occupants’ needs as determined by OCC.…”
Section: Background and Previous Workmentioning
confidence: 99%
“…Based on the MATLAB simulation for a single zone in three typical days (i.e., cold, hot, and mild), Goyal et al found HVAC energy savings of approximately 50% for that zone, relative to the baseline terminal control that had a minimum airflow rate fixed at 40% of the terminal box design flow rate. This rule-based OBC strategy was further tested in a campus building in Gainesville, FL [24]. The field test was performed on 12 fully actuated zones (i.e., each zone is served by a single terminal box) for six consecutive days in April.…”
Section: Previous Related Workmentioning
confidence: 99%
“…To save energy, VAV systems regulate airflow according to the current needs in a ventilated zone [8,9]. When less air is needed, less energy is consumed by the system.…”
Section: Introductionmentioning
confidence: 99%
“…Energies 2020, 13, 4947; doi:10.3390/en13184947 www.mdpi.com/journal/energies Equation 1shows that VAV systems have energy-saving potential. However, when lowering the airflow, the system may not be able to remove all the contaminants [9] and may cause their accumulation within buildings, leading to dead zones [9]. The recommended parameters for systems with variable air flow, including the fresh air rate and criteria for the indoor environment (thermal, air quality, noise, light), are provided by standards EN 15251:2012 [17], ISO 7730 [18], and ANSI/ASHRAE-62.1 [19].…”
Section: Introductionmentioning
confidence: 99%